Neurovascular Imaging MRI & Microangiography - Takahashi, Shoki; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2011)
The comparison of MR images and cadaver microangiograms of the basal perforating arteries is crucial for understanding the courses and supply areas of these vessels and in turn, for diagnosing pathologies in this region. Divided into three sections- normal anatomy of brain vessels; neurovascular imaging in pathology; and anatomy and imaging of spinal vessels- Neurovascular Imaging contains a rich collection of images to teach the reader how to interpret MR images of the brain vessels and spinal vessels, and how to identify pathologies. Written and edited by a group of highly acclaimed experts in the field, Neurovascular Imaging is an authoritative account of the interpretation of MR images of the brain vessels and spinal vessels, and is a valuable addition to the library of the diagnostic radiologist.
Intracranial Arterial System: The Main Trunks and Major Arteries of the Cerebrum -- Intracranial Arterial System: Basal Perforating Arteries -- Intracranial Arterial System: Infratentorial Arteries -- Perforating Branches of the Anterior Communicating Artery: Anatomy and Infarcation -- Cerebral Arterial variations and anomalies diagnosed by MR Angiography -- Regional MR Perfusion Topographic Map of the Brain using Arterial Spin Labeling (ASL) at 3 Tesla -- Normal anatomy of Intracranial Veins: Demonstration with MR angiography, 3D-CT Angiography and Microangiographic Injection Study -- Mapping Superficial Cerebral Veins on the Brain Surface -- Preoperative Visualization of the Lenticulostriate Arteries Associated with Insulo-opercular Gliomas Using 3-T Magnetic Resonance Imaging -- Ischemic Complications Associated with Resection of Opercular Gliomas -- Imaging and Tissue Characterization of Atherosclerotic Carotid Plaque using MR Imaging -- MR Imaging of Cerebral Aneurysms -- MR Imaging of Vascular Malformations -- Cerebral Venous Malformations -- Thrombosis of the Cerebral Veins and Dural Sinuses -- Vessels of the Spine and Spinal Cord: Normal Anatomy -- MDCT of the artery of Adamkiewicz -- Magnetic Resonance Angiography of the Spinal Cord Blood Supply -- Magnetic Resonance Imaging of Spinal Vascular Lesions.
Keywords: Medicine; Radiology, Medical; Angiography; Neurology; Medicine & Public Health; Imaging / Radiology; Diagnostic Radiology; Neuroradiology; Angiology; Neurology